Exploring adaptive capacity: Observations from the vulnerable human-coastal environmental system of the Bay of Bengal in India - Datta, Satabdi; Roy, Joyashree (Frontiers in Climate, 2022)
This article presents the factors that help building adaptive capacity of individuals to reduce vulnerability from natural threats. The findings are based on primary data on individuals engaged in various livelihood practices in Digha-Sankarpur- Mandarmoni region along the eastern coastline of Bay of Bengal in India. Coastal community have their individual perceptions about their vulnerability to natural threats and associated risks to various assets. Based on perception survey responses, ‘adaptive capacity’ is measured and the determining factors are analysed with an aim to provide policy guidelines for strengthening adaptive capacity of people dependent on coastal ecosystem based livelihoods. Findings show that income security for individuals in coastal system can be achieved through livelihood diversification strategy. The scope for individuals to build personal savings, access to financial institutions and collaborative actions with immediate neighbours in the community help to prevent multiple losses at the individual level. Government actions to provide institutional and governance support and incentives to promote livelihood diversification and personal savings would enhance adaptive capacity through institutional actions. Public investment in public goods and services including protection and monitoring of natural coastal ecosystems, infrastructure development, technological intervention, providing access to information, community empowerment have important role to play in enhancing adaptive capacity.